AMOTORIK KASAR ANAK DAN PERMAINAN MELEMPAR BOLA SASARAN - Yanti, Ika Febri; Mashar, Riana; Hermahayu, Hermahayu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2015)
The purpose of this study to determine whether there is an increase in gross motor skills by playing on the target to throw the ball in children.This research is a classroom action research conducted during two cycles, wherein each cycle consists of four steps: planning, execution, observation and evaluation. 16 children as research subjects in this study were students in group B at ¬kanak Pertiwi Nursery Trenten Magelang. Variables used include input variables (ability motororik initial coarse), the process variables (target ball throwing game) and output variables (ability motororik rough end). Data collection methods used in this research is the method of observation. The research instrument used was the observation sheet. The validity of the instrument using a test technique expert or professional judgment in early childhood expert Lecturer’s and chairman of the Association of Teachers of kindergarten District of Candimulyo. Data analysis techniques used in this action research is descriptive data analysis techniques and percentages.The research proves that the game throwing the ball the goal could improve gross motor skills in children. Results of preliminary observations note that the average achievement of new subjects Rough Motoric capabilities reached 64.4%, still far from the target to be achieved is 75%. After learning activities using the target to throw the ball in cycle 2, the average achievement Rough Motoric capabilities subjects increased to 94.4%. All indicators of the ability of Motor Coarse been achieved well. Thus the hypothesis that the game throwing the ball the goal could improve gross motor skills in children are accepted.